1997
DOI: 10.1046/j.1464-410x.1997.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐flow studies in the diagnosis of bladder outlet obstruction: a study comparing suprapubic and transurethral techniques

Abstract: Objective To compare suprapubic and transurethral 60% of men were in the same LPURR class with either method. Using the transurethral method, 26% of methods of measuring intravesical pressure in a group of men undergoing investigation for lower urinary patients increased the LPURR class by one and 6% by two classes. Using the Abrams-GriÃths nomogram, tract symptoms (LUTS), to identify which urodynamic variables are aÂected by the presence of an urethral 17% moved from a classification of equivocal to obstructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 3 publications
(5 reference statements)
2
9
0
Order By: Relevance
“…There were significant differences between the mean values of the two methods for Qmax, Pdet, Qmax, [8]. Indeed, pressure-flow analysis has been generally accepted as the gold standard in measuring outcome and certainly in quantifying the grade of BOO [3,5], and it has been verified significant for both diagnosis before surgical treatment and evaluation after operation, such as before and after transurethral resection of prostate [9,10]. Therefore, it is very important to get precise results from the examination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were significant differences between the mean values of the two methods for Qmax, Pdet, Qmax, [8]. Indeed, pressure-flow analysis has been generally accepted as the gold standard in measuring outcome and certainly in quantifying the grade of BOO [3,5], and it has been verified significant for both diagnosis before surgical treatment and evaluation after operation, such as before and after transurethral resection of prostate [9,10]. Therefore, it is very important to get precise results from the examination.…”
Section: Resultsmentioning
confidence: 99%
“…During pressure-flow studies intravesical pressure can be measured using either transurethral or suprapubic lines. The transurethral method is generally used, but the suprapubic route has the theoretical advantage of leaving the urethra untouched during the measurements and, therefore, might preclude any artifacts produced by instrumentation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Walker et al [13] compared a suprapubic catheter with a transurethral catheter for pressureflow studies and concluded that transurethral catheters created a statistically significant increase in the degree of obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Free uro£owometry, measurement of residual urine, ¢lling cystometry at a rate of 30 ml/min, and pressure/ £ow study of micturition were included in the study. During the latter, the urethra was catheter-free and the intravesical pressure recorded via a ¢ne suprapubic catheter (18G epidural catheter) in order to have pressure-£ow studies without any arti¢cial outlet obstruction [Walker et al, 1997].…”
Section: Urodynamic Studiesmentioning
confidence: 99%